The impact of auditory working memory training on the fronto-parietal working memory network - Schneiders, Julia; Opitz, Bertram; Tang, Huijun; Deng, Yuan; Xie, Chiaoxiang; Li, Hong; Mecklinger, Axel (Frontiers in Human Neuroscience, 2012)
Working memory training has been widely used to investigate working memory processes. We have shown previously that visual working memory benefits only from intra-modal visual but not from across-modal auditory working memory training. In the present functional magnetic resonance imaging study we examined whether auditory working memory processes can also be trained specifically and which training-induced activation changes accompany theses effects. It was investigated whether working memory training with strongly distinct auditory materials transfers exclusively to an auditory (intra-modal) working memory task or whether it generalizes to an (across-modal) visual working memory task. We used an adaptive n-back training with tonal sequences and a passive control condition. The memory training led to a reliable training gain. Transfer effects were found for the (intra-modal) auditory but not for the (across-modal) visual 2-back task. Training-induced activation changes in the auditory 2-back task were found in two regions in the right inferior frontal gyrus. These effects confirm our previous findings in the visual modality and extends intra-modal effects to the auditory modality. These results might reflect increased neural efficiency in auditory working memory processes as in the right inferior frontal gyrus is frequently found in maintaining modality-specific auditory information. By this, these effects are analogical to the activation decreases in the right middle frontal gyrus for the visual modality in our previous study. Furthermore, task-unspecific (across-modal) activation decreases in the visual and auditory 2-back task were found in the right inferior parietal lobule and the superior portion of the right middle frontal gyrus reflecting less demands on general attentional control processes. These data are in good agreement with across-modal activation decreases within the same brain regions on a visual 2-back task reported previously.